Development and feasibility testing of an avatar‐based education application for patients with acute coronary syndrome. Issue 19 (30th July 2018) - Tongpeth, Jintana; Du, Hui Yun; Clark, Robyn A.
Abstract: Aims: To develop and evaluate an interactive, avatar‐based education application, for improving patients' knowledge of, and response to, acute coronary syndrome (ACS) symptoms. Background: A patient's ability to recognise and respond to the symptoms of ACS is imperative for seeking timely medical intervention. Innovative patient education interventions are needed to support patient education and patient self‐care. Methods: Participatory action research methods were used to engage consumers with cardiac and information technology (IT) experts to develop an avatar‐based education application. The avatar‐based education application was developed according to evidence‐based guidelines. The effect on ACS knowledge was evaluated in a group of ten patients with ACS. Results: In total, 10 consumers with ACS and 12 cardiovascular clinical and IT experts participated in the designing and development of the education application. An additional 10 consumers (mean age was 52.2 ± 10.4 years) were recruited for testing the feasibility of the application on improving ACS knowledge. A high level (87.3%) of satisfaction was reported with a 15.7% increase in the knowledge subscale score of the ACS Response Index and 25.7% increase in belief scores, while symptom recognition scores increased by 24.2%. Conclusion: An avatar‐based application for heart attack education is feasible and has the potential to support patient education by enhancing engagement and improving health literacy. These outcomes will provide preliminary data for an effectiveness trial. Relevance to clinical practice: Nurses frequently experience obstacles in providing patient education, such as health literacy and language barriers. Utilising avatar‐based technology could potentially support the delivery of patient education. Involving consumers in the development these innovative educational tools is essential. Consumer participation in design has improved the engagement, satisfaction and outcomes of our app.